Maximum Power Point Tracking for a Grid Connected Photovoltaic System using Sliding Mode Control - D. Sattianadan; V. Kalyanasundaram; S. Vidyasagar; Deepak Kumar Nayak; Roopam Jha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents a method to track the maximum power point for an isolated grid connected photovoltaic system. The method used to achieve this goal is sliding mode control. A high frequency flyback converter topology working in continuous conduction mode is used to boost the voltage and also provides galvanic isolation between input and output side. An inverter is used to invert the power for a grid connected operation. Therefore, the primary objective of this study is to design a sliding mode controller which can track maximum power driving a high frequency flyback converter and demonstrate its practicality as a higly efficient maximum power point tracker. This system is modelled and tested in MATLAB SIMULINK. To verify the results a practical implementation of sliding mode controller with high frequency flyback transformer is performed in a hardware setup